2020
DOI: 10.1042/bsr20194142
|View full text |Cite
|
Sign up to set email alerts
|

LHPP suppresses proliferation, migration, and invasion and promotes apoptosis in pancreatic cancer

Abstract: Pancreatic cancer (PaCa) is a common malignant tumor of the digestive system with poor prognosis and no ideal treatment for inoperable patients, which is partly due to delayed diagnoses. It is recently reported that the protein histidine phosphatase LHPP is a tumor suppressor in hepatocellular carcinoma, cervical cancer, and bladder cancer. So far, there is no study on the expression level of LHPP in PaCa, and its mechanism of action on tumors is unclear. In this experiment, LHPP expression was lower in cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…In bladder cancer, LHPP inhibits cell growth in vitro and in vivo via regulating the AKT/p65 signaling pathway [14]. In pancreatic cancer, LHPP suppresses cell proliferation and metastasis and promotes cell apoptosis via interacting with the PTEN/AKT signaling pathway [15]. However, the biological function of LHPP in RCC remains unknown.…”
mentioning
confidence: 99%
“…In bladder cancer, LHPP inhibits cell growth in vitro and in vivo via regulating the AKT/p65 signaling pathway [14]. In pancreatic cancer, LHPP suppresses cell proliferation and metastasis and promotes cell apoptosis via interacting with the PTEN/AKT signaling pathway [15]. However, the biological function of LHPP in RCC remains unknown.…”
mentioning
confidence: 99%
“…LHPP reduction promoted bladder cancer cell proliferation and growth by mediating the AKT/p65 signaling pathway [ 18 ]. In pancreatic cancer, enhanced LHPP expression restored PTEN protein and repressed the AKT phosphorylation resulted to inhibition of PaCa (Pancreatic cancer) progression and metastasis [ 17 ]. Wang et al [ 19 ] illustrated that LHPP could not only repress aggressive phenotype but also trigger autophagy in papillary thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholysine phosphohistidine inorganic pyrophosphate phosphatase (LHPP) , a type of histidine phosphatase protein, has been proven as a tumor suppressor in hepatocellular carcinoma [ 15 ] (HCC), cervical [ 16 ], pancreatic [ 17 ], bladder [ 18 ], and thyroid cancers [ 19 ] by regulating the AKT signaling pathway. In the previous research [ 20 ], LHPP protein overexpression was highly related to better prognosis and lower tumor–node–metastasis classification of patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…acts as a tumor suppressor in liver cancer where its expression is downregulated, whereas pNME1/2 are upregulated, resulting in increased histidine phosphorylation of proteins [126]. Other studies in colorectal [127], bladder [128], pancreatic [129], thyroid [130] and cervical cancer [131] have demonstrated that LHPP. is downregulated in cancer [132].…”
Section: Histidine Phosphatasesmentioning
confidence: 99%